2006
DOI: 10.1111/j.1470-6431.2006.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Household production of sorghum beer in Benin: technological and socio‐economic aspects

Abstract: This study evaluated the sorghum brewing microenterprises in Benin with emphasis on the beer quality, the social significance of the product as well as the income generated. Tchoukoutou, the Benin opaque sorghum beer, has important social functions as it fosters the cooperative spirit and remains an ancestral beverage widely used for traditional ceremonies. The manufacturing process consists of malting (soaking, germination and sun drying), brewing (mashing, boiling, filtration) and fermentation. The beer is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 16 publications
2
28
1
14
Order By: Relevance
“…Traoré et al, (2004) reported that in order to enhance energy value of gruel in order to meet nutritional requirements of young children, malted cereal flour should be added to infant flour in rate depending on raw material. These observations were in lined with those found by Kayodé et al, (2006) who reported that the malted maize flour is a good base in the preparation of infant gruel with good energy value. (Brou, 2000).…”
Section: Fig1supporting
confidence: 80%
See 2 more Smart Citations
“…Traoré et al, (2004) reported that in order to enhance energy value of gruel in order to meet nutritional requirements of young children, malted cereal flour should be added to infant flour in rate depending on raw material. These observations were in lined with those found by Kayodé et al, (2006) who reported that the malted maize flour is a good base in the preparation of infant gruel with good energy value. (Brou, 2000).…”
Section: Fig1supporting
confidence: 80%
“…This study is to firstly show, the use of local germinated maize and sorghum and baobab pulp which has improved the bioavailability of minerals in germinated infant flours. This could mean that germination processes are likely to improve bioavailability of minerals b etter than fermentation (Syed et al, 2011;Sanoussi et al, 2013 andAmoin et al, 2015).This is due to the fact that germination is likely to increase the r etention of minerals (Helland et al, 2002;Traoré et al, 2004).This bioavailability of minerals in germinated infant flours was due to the ability of the germination technique to reduce phytate levels in infant flours (Traoré et al, 2004;Kayodé et al, 2006). Anigo et al, (2010) have found iron, magnesium, calcium, and zinc in germinated maize and sorghum flours enriched with groundnut and soybean, respectively of 23.98mg, 148.91mg, 47.66 mg and 7.88 mg.…”
Section: Fig1mentioning
confidence: 99%
See 1 more Smart Citation
“…Lactic acid bacteria and yeasts have been reported (Kayodé et al, 2007) to be the major microorganisms involved in the fermentation of tchoukoutou. These fermentation microorganisms have been reported to possess probiotic effects, to reduce the level of pathogenic bacteria occurring in beverages and to reduce the severity duration and morbidity of diarrhea (Mensah et al, 1991;Kimmons et al, 1999).…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 99%
“…Cette activité revêt une importance socio-économique considérable, en particulier pour les femmes des localités concernées. Kayodé et al (2007) ont attribué ce caractère socio-économique remarquable de la production de la bière de sorgho à son utilisation abondante au cours des cérémonies traditionnelles. De plus, elle constitue une importante source de revenus pour les femmes qui la produisent à l'échelle locale, en utilisant la technologie traditionnelle.…”
Section: Introductionunclassified